Lymphatic Permeation Predicts Systemic Recurrence in Combination with Vascular Involvement in Laparoscopically Resected N0 Colon Cancer. Issue 12 (December 2017) - Kojo, Ken; Katoh, Hiroshi; Naito, Masanori; Yamashita, Keishi; Nakamura, Takatoshi; Sato, Takeo; Yamanashi, Takahiro; Watanabe, Masahiko
High-risk patient selection is required in N0 colon cancer. Although a number of studies have suggested high-risk clinicopathological predictors, most of these are based on analyses in heterogeous patients in terms of surgical procedures. Laparoscopic surgery for colon cancer is becoming a standard procedure worldwide because of its less invasiveness. Accordingly, we aimed to identify bona fide high-risk factors of recurrence in homogeneous N0 patients who underwent laparoscopic surgery. Two hundred and twenty-five patients who underwent laparoscopic curative resection for N0 colon cancer were analyzed. Clinicopathological parameters were tested for their relation to survival. The 5-year recurrence-free survival rate (RFS) was 96.1 per cent. Lymphatic involvement (P < 0.001), vascular involvement (P = 0.007), and size of tumor (P = 0.023) were significantly associated with worse prognosis in the univariate analyses. Lymphatic involvement was the independent prognostic factor associated with RFS in the multivariate analysis (P = 0.013). Importantly, lymphatic involvement predicts detrimental prognosis only when vascular involvement is present. The RFS of the patients with both lymphatic and vascular involvement was 88.9 per cent, whereas it was 100 per cent in the counterpart. Differentiation, vascular involvement preoperative carcinoembryonic antigen, and CA 19-9 levels were significantly associated with lymphatic involvement in a multivariate logistic regression analyses. The present study concludes that lymphatic involvement in the presence of vascular involvement may be a high risk for systemic recurrence in the laparoscopically resected N0 colon cancer.